Accountability in public policy partnerships - Julia Steets (Palgrave Macmillan, 2010)
Public-private partnerships have become an important tool for delivering essential public goods, but critics fear that they erode public accountability. Making partnerships more accountable requires a clear understanding of what accountability means for partnerships and which mechanisms can be used to strengthen it.Accountability in Public Policy Partnerships develops a new model of accountability based on principal-agent theory. This model provides a firm normative foundation for accountability demands. At the same time, it shows which accountability standards apply to which kinds of partnerships. Norm-setting partnerships, for example, require strong mechanisms for participation, whereas implementation partnerships must focus on performance evaluation, competitive bidding and beneficiary feedback processes. The accountability model and standards developed in this book provide a guide for partnership practitioners who are developing the governance structures of their partnerships; they serve as benchmarks for evaluating partnerships; and they provide new inputs for the ongoing accountability debates in the public, the corporate and the civil society sectors.
Keywords: 350; Principal-agent theory; Accountability; Public policy; Öffentlich-private Partnerschaft; Öffentliches Rechnungswesen